CONTINUING TEACHER TRAINING FOR THE USE OF ELECTRONIC MEDIA - Lima Cangirana de Jesus, Dináurea; Wendel Santana Coêlho, Márcio (Revista Gênero e Interdisciplinaridade, 2022)
Electronic media are increasingly present in the lives of teachers and students, but their use in teaching is still very restricted or often non-existent. We present in this study an analysis of the use of electronic media in the classroom by teachers. For that, it used the theoretical references of Almeida (2000); Behrens (2001); Coast (2005); Fantin (2006); Fischer (2007), as well as LDB, Moran, PCNs and Perrenoud (2000). The research methodology used privileged the bibliography. The research results point to the need for investment in initial and continuing education, which can contribute to the implementation of projects aimed at the use of electronic media in the school environment.